Adjunctive stent use during endovascular intervention to the femoropopliteal artery with drug coated balloons: Insights from the XLPAD registry. (August 2018) - Kokkinidis, Damianos G; Jeon-Slaughter, Haekyung; Khalili, Houman; Brilakis, Emmanouil S; Shammas, Nicolas W; Banerjee, Subhash; Armstrong, Ehrin J
With growing use of drug-coated balloons (DCB) for femoropopliteal (FP) artery interventions, there is limited information on rates of real-world adjunctive stent use and its association with short and long-term outcomes. We report on 225 DCB treated FP lesions in 224 patients from the Excellence in Peripheral Artery Disease (XLPAD) registry (NCT01904851) between 2014 and 2016. Cochran–Mantel–Haenszel and Wilcoxon rank sum statistics were used to compare stented (planned or 'bail-out') versus non-stented DCB treated lesions. Stents were implanted in 31% of FP DCB interventions. Among the 70 stents implanted, 46% were for 'bail-out' indications and 54% were planned. Lesions treated with stents were longer (mean 150 mm vs 100 mm; p < 0.001) and less likely to be in-stent restenosis lesions (10% vs 28%; p =0.003). Stenting was significantly more frequent in complex FP lesions, including chronic total occlusions (66% vs 34%; p < 0.001). For bail-out stenting, interwoven nitinol stents were the most common type (50%) followed by drug-eluting stents (34%) and bare-metal stents (22%). There were no differences in peri-procedural complication rates or 12-month target limb revascularization rates (18.6% vs 11.6%; p =0.162) or 12-month amputation rates (11.4% vs 11%; p =0.92) between lesions where adjunctive stenting was used versus lesions without adjunctive stenting, respectively. In conclusion, in a contemporary 'real-world' adjudicated multicenter US registry, adjunctive stenting was necessary in nearly a third of the lesions, primarily for the treatment of more complex FP lesions, with similar short and intermediate-term clinical outcomes compared with non-stented lesions.ClinicalTrials.gov Identifier: NCT01904851